People's Economy and Employment Resilience Amidst Population Growth - Rohman, Abdul; Pramesti, Desta Wulandari; Wati, Eliya; Noviarita, Heni (Lentera Ilmu Nusantara, 2024)
This article discusses population dynamics and employment challenges in Indonesia, as well as strategies for developing a people's economy as a solution to create a productive and quality workforce. Rapid population growth has consequences for the employment structure, which requires increased skills and empowerment of the workforce. This article highlights the important role of education, especially vocational education, in equipping the workforce with relevant and competitive skills. In addition, empowering women in the employment sector and strengthening MSMEs through digitalization are important elements in realizing an inclusive economy. The impact of the COVID-19 pandemic is also discussed as a factor that accelerates the need for adaptation and innovation in the employment sector. Strategies for developing a people's economy such as strengthening cooperatives, digitalizing MSMEs, and developing local potential are expected to be able to create sustainable jobs and reduce economic inequality. This article uses a number of references from Heni Noviarita to support the analysis and policy recommendations in the context of population and employment in Indonesia.